Answer:
Assuming you want to simplify the expression, it can be shortened to:
-k² - 2k
Step-by-step explanation:
What you need to do here is called grouping like terms. Like terms can be described as terms that have the same factors. In this case, the factors we're looking at are k and k²:
Given:
k - 3k² -3k + 2k²
We'll rearrange to group like expressions:
= -3k² + 2k² + k -3k
Pull out common factors:
= (-3 + 2)k² + (1 - 3)k
And simplify:
= -k² - 2k
1.45X=0
1.45 1.45
U divide 1.45 in each side 1.45 divided by 1.45 =x
And 1.45 divided by 0 is of course 0 cuz anything divided or
Multiplied by 0 Is always 0
Ur answer is X=1.35
Explanation:
Pair 1 is true if Jeff's monthly income is $600/20% = $3,000.
Pair 2 is true if Jeff's monthly income is $1200/10% = $12,000.
Both pairs can be true if Jeff's monthly income increased by a factor of 4 in the 20 years from 1990 to 2010.
Obviously, Jeff spent more on housing in 2010. (Fortunately for Jeff, that larger expenditure was a smaller fraction of his income.)
23 the answer is Bbbbbbbbbbbbbbbbbbbb